Factors influencing patient satisfaction with dental appearance and treatments they desire to improve aesthetics - Hassan Nurhidayati; Saddki Norkhafizah; Tin-Oo Mon (BMC, 2011)
Abstract Background We assessed factors influencing patients' satisfaction with their dental appearance and the treatments they desired to improve dental aesthetics. Methods A cross-sectional study was performed out among 235 adult patients who visited the Hospital Universiti Sains Malaysia dental clinic. A structured, interviewer-guided questionnaire was used to identify patient satisfaction with their general dental appearance, cosmetic elements and desired treatments. Results The 235 patients consisted of 70 males (29.8%) and 165 females (70.2%), of mean age 31.5 years (SD 13.0). Of these patients, 124 (52.8%) were not satisfied with their general dental appearance. In addition, 132 patients (56.2%) were not happy with the color of their teeth, 76 (32.3%), regarded their teeth were poorly aligned, 62 (26.4%), as crowded and 56 (23.4%) protruded. Dissatisfaction with tooth color was significantly higher in female than in male patients (odds ratio [OR] of 1.99 (95% confidence interval [CI] 1.13-3.50). Tooth whitening was the treatment most desired by patients (48.1%). Results of multiple logistic regression analysis showed that patient dissatisfaction with general dental appearance was significantly associated with female gender (OR = 2.18; 95% CI: 1.18-4.03), unhappiness with tooth color (OR = 3.05; 95% CI: 1.74-5.34) and the opinion that their teeth protruded (OR = 2.91, 95% CI: 1.44-5.91). Conclusions Most patients in this study were not satisfied with their dental appearance with a greater percentage of females expressing dissatisfaction than males. An age was not associated with satisfaction. Unhappiness with tooth color and feelings of having protruding teeth also had a significant negative influence on patient satisfaction with general dental appearance.